SISTEM INFORMASI AKUNTANSI PROSES BISNIS JOB ORDER PADA PERUSAHAAN JASA - Purwatiningsih, Esty; Sumarna, Alfonsa Dian (Jurnal Riset Keuangan dan Akuntansi, 2024)
Accounting information systems are very important for newly established micro start-ups. Especially operational standards for main business processes. This can help start-ups carry out their business processes in a structured, orderly, controlled, and standardized manner. This applied research discusses the preparation of job order procedures that can be applied to a micro start-up business in production house services. This research aims to create accounting information systems and organize a simple job order transaction workflow with robust internal control. Procedures are prepared narratively and in flowchart form for each job order type transaction that occurs by applying the principles of effective and efficient internal control. This research method is descriptive qualitative. It can be concluded that micro start-up businesses need to have job order procedures in the form of written narratives or the form of flowcharts and also bookkeeping, which contain elements of an internal control system to adapt to the limited resources available in this micro start-up business. Keywords: Accounting Information System, Job Order, Business Process